giup mik
c)\(\left(x-\frac{2}{7}\right)\left(0,5x^2+\frac{3}{4}\right)=0\)
d)\(\left(\frac{-5}{4}x+3,25\right)\left[\frac{3}{5}-\left(\frac{-5}{2}x\right)\right]=0\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Trả lời:
a, \(3\left|x\right|+2=5\)
\(\Leftrightarrow3\left|x\right|=3\)
\(\Leftrightarrow\left|x\right|=1\)
\(\Leftrightarrow\orbr{\begin{cases}x=1\\x=-1\end{cases}}\)
Vậy x = 1; x = - 1
b, \(4-\left|x\right|=\frac{1}{4}\)
\(\Leftrightarrow\left|x\right|=\frac{15}{4}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{15}{4}\\x=-\frac{15}{4}\end{cases}}\)
Vậy x = 15/4; x = - 15/4
c, \(4+\left|2x\right|=\frac{2}{3}\)
\(\Leftrightarrow\left|2x\right|=\frac{10}{3}\)
\(\Leftrightarrow\orbr{\begin{cases}2x=\frac{10}{3}\\2x=-\frac{10}{3}\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{5}{3}\\x=-\frac{5}{3}\end{cases}}}\)
Vậy x = 5/3; x = - 5/3
d, \(3\left|x\right|=\frac{1}{7}-\frac{1}{8}\)
\(\Leftrightarrow3\left|x\right|=\frac{1}{56}\)
\(\Leftrightarrow\left|x\right|=\frac{1}{168}\)
\(\Leftrightarrow\orbr{\begin{cases}x=\frac{1}{168}\\x=-\frac{1}{168}\end{cases}}\)
Vậy x = 1/168; x = - 1/168
a, \(|-2,1|\)\(=2,1\)
b,\(|-\)\(\frac{2}{9}|\)\(=\frac{2}{9}\)
c,\(|12,2|\)\(=12,2\)
d,\(|0|\)\(=0\)
e,\(|\frac{3}{2}|\)=\(\frac{3}{2}\)
Hok tốt~
\(\frac{3}{11}:-\frac{9}{5}+\frac{3}{11}:-\frac{18}{13}\)
\(=\frac{3}{11}\cdot-\frac{5}{9}+\frac{3}{11}\cdot-\frac{13}{18}\)
\(=\frac{3}{11}\cdot\left(-\frac{5}{9}+-\frac{13}{18}\right)\)
\(=\frac{3}{11}\cdot-\frac{23}{18}\)
\(=-\frac{23}{66}\)
\(\frac{2x-5}{y+1}=\frac{x-1}{3y}=\frac{1}{3}\Rightarrow\hept{\begin{cases}3\left(2x-5\right)=y+1\\x-1=y\end{cases}}\)
\(\Rightarrow6x-15=x-1+1\)
\(\Leftrightarrow x=3\)
suy ra \(y=2\).
Trả lời:
c, \(\left(x-\frac{2}{7}\right)\left(0,5x^2+\frac{3}{4}\right)=0\)
\(\Leftrightarrow x-\frac{2}{7}=0\) ( vì \(0,5x^2+\frac{3}{4}\ge\frac{3}{4}>0\forall x\) )
\(\Leftrightarrow x=\frac{2}{7}\)
Vậy x = 2/7
d, \(\left(-\frac{5}{4}x+3,25\right)\left[\frac{3}{5}-\left(-\frac{5}{2}x\right)\right]=0\)
\(\Leftrightarrow\left(-\frac{5}{4}x+3,25\right)\left(\frac{3}{5}+\frac{5}{2}x\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}-\frac{5}{4}x+3,25=0\\\frac{3}{5}+\frac{5}{2}x=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=\frac{13}{5}\\x=-\frac{6}{25}\end{cases}}}\)
Vậy x = 13/5; x = - 6/25
c)(x−27 )(0,5x2+34 )=0
d)(−54 x+3,25)[35 −(−52 x)]=0